Procrastination is not only a “thief of time”, but also a thief of happiness: It buffers the beneficial effects of telework on well-being - Junça Silva, A.; Neves, P.; Caetano, A. (International Journal of Manpower, 2024)
This study draws on the affective events theory to understand how telework may influence workers’ well-being. Hence this study aimed to (1) analyze the indirect relationship between telework and well-being via daily micro-events, and (2) test whether procrastination would moderate this indirect effect. To test the goals, data was gathered from a sample of teleworkers in the IT sector (N=232). To analyze the data, a moderated mediation analysis was performed in SPSS with PROCESS macro. The results showed that micro-daily events mediated the positive relationship between telework and well-being; however, this relation was conditional upon the levels of workers’ levels of procrastination, that is, this link became weaker for those who were procrastinators. By highlighting the importance of telework, daily micro-events, and procrastination, this study offers managers distinct strategies for enhancing their employees' well-being. Despite the existing research investigating the effect of telework on well-being, studies investigating the intervening mechanisms between these two constructs are scarce. Moreover, there is a lack of research investigating the moderating effect of procrastination in these relations. Hence, this study fills these gaps and advances knowledge on the process that explains how (via daily micro-events) and when (when procrastination is low) teleworking influences workers’ well-being.